Immunohistochemical and mRNA localization of the angiotensin II receptor subtype 2 (AT2) in follicular granulosa cells of the rat ovary - Obermüller, Nicholas; Gentili, Monika; Gauer, Stefan; Gretz, Norbert; Weigel, Michael; Geiger, Helmut; Gaßler, Nikolaus (Journal of histochemistry & cytochemistry, 2004)
A local renin-angiotensin system (RAS), including specific angiotensin II receptor subtypes, is present in the rat ovary. Immunohistochemistry using a polyclonal antibody and mRNA in situ hybridization were performed on perfusion-fixed, paraffin-embedded ovaries obtained from untreated sexually mature, normally cycling rats. Immunofluorescent staining revealed an exclusive and distinct labeling of follicular granulosa cells showing a plaque-like expression pattern at the cell borders, being detectable in different stages of atretic degeneration. On adjacent sections the expression of the respective mRNA could be shown in granulosa cells of the same follicle. The AT2 receptor may be implicated in the ovarian atretic process by influencing follicular cell-cell communication.